Efforts To Improve Students' Mathematical Communication Ability Through Reciprocal Teaching Learning Model For Class VIII SMPS Development National School Of Milk Base - Dahlan, Yulia; Siregar, Nurhasanah (Green Publisher Indonesia, 2022)
This study aimed to determine the improvement of students' mathematical communication skills in relation and function materials through the Reciprocal Teaching learning model in class VIII of SMPS National Development Pangkalan Susu. The researchers used classroom action research (CAR) which is carried out in 2 cycles, each cycle was carried out in 2 meetings. The subjects in this study were students of class VIII of SMPS National Development Pangkalan Susu, totaling 22 people. Data collection techniques used were teacher and student observation sheets, and tests of mathematical communication skills. The test was carried out 3 times, namely a diagnostic test, a test for mathematical communication skills I, and a test for mathematical communication skills II. The results of the research at the time of the diagnostic test showed that the students' mathematical communication skills in explaining/writing the elements were known, the elements were asked and concluded correctly and completely (33.4%), painting pictures, diagrams, graphs, or tables completely and correctly (38%), and express mathematical ideas using symbols or mathematical language in writing as a complete and correct representation of an idea or ideas (32%). After being given action in Cycle I and Cycle II, the students were able to explain/write known elements, ask questions and conclusions correctly and completely, describe pictures, diagrams, graphs, or tables completely and correctly, and state mathematical ideas using symbols or mathematical language in writing as a complete and correct representation of an idea or idea. The results of the mathematical communication ability test given in the classical cycle I obtained that students who completed were 10 students (45.45%) out of 22 students with an average of 58.09, in the second cycle who completed increased to 16 students from 22 students (81 ,81%) with an average of 74.18 and has achieved the classical completeness criteria because 80% of the number of students have mathematical communication skills in the sufficient category, namely 70. Based on the results of the study, it can be concluded that the Reciprocal Teaching model can improve students' mathematical communication skills in SMPS National Development of Pangkalan Susu.